High-water-absorption antibacterial bath towel fabric and preparation method thereof
By using cotton fiber, bamboo charcoal fiber and polyester in the bath towel fabric, the quaternized modified composite antibacterial agent with active functional groups, the problem of bath towels being difficult to quickly dry and breed bacteria is solved, and the effect of high water absorption, antibacterial and water-resistant washing is achieved , improves the hygiene and user experience of the product.
Patent Information
- Application Number
- CN202411217494.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Bath towels on the market have good water storage properties but are difficult to dry quickly, which is prone to bacteria and produces odor, and lacks effective antibacterial and deodorizing properties.
Using highly absorbent antibacterial bath towel fabric, containing cotton fiber, bamboo charcoal fiber, polyester and quaternized modified composite antibacterial agent with active functional groups, the antibacterial layer is formed through the synergistic effect of silver cerium doping titanium dioxide and coupling agent, and the water absorption is improved. , antibacterial properties and water-resistant properties.
It realizes the rapid water absorption, antibacterial, long-lasting deodorization and water-resistant performance of bath towels, keeping them clean and hygienic, and improving the user experience.
Smart Images

Figure BDA0005021971800000111 
Figure BDA0005021971800000112
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of textiles, and in particular to a highly water-absorbent and antibacterial bath towel fabric and a preparation method thereof. Background Art
[0002] Bath towels are a type of towel. The height and density of the terry loops are higher and denser than those of face towels and pillow towels. They are better at absorbing water and keeping warm than other towels. They are mainly used to wipe the body and cover the body after bathing, and are also often used to cover the body to prevent cold. However, the bath towels on the market have good water storage capacity and cannot achieve the effect of quick drying. They are often in a damp state. At the same time, they are placed in an environment where it is difficult to see sunlight, which makes it very easy to breed bacteria and have a bad smell after a while. Based on this, it is particularly important to provide a bath towel that is water-absorbent, quick-drying, antibacterial, long-lasting deodorizing, and washable. Summary of the invention
[0003] In order to solve the above technical problems in the prior art, the present application provides a highly water-absorbent and antibacterial bath towel fabric and a preparation method thereof.
[0004] In the first aspect, a highly absorbent antibacterial bath towel fabric adopts the following technical solution: A highly water-absorbent antibacterial bath towel fabric comprises the following raw materials, measured by weight: 40-45 parts of cotton fiber, 30-36 parts of bamboo charcoal fiber, 50-56 parts of polyester, 20-25 parts of a hydrophilic finishing agent, and 5-6 parts of a quaternary ammonium modified composite antibacterial agent with an active functional group, wherein the quaternary ammonium modified composite antibacterial agent with an active functional group uses silver-cerium-doped titanium dioxide, a quaternary ammonium salt, and a coupling agent as main raw materials, firstly, the quaternary ammonium salt and the silver-cerium-doped titanium dioxide are reacted at an addition ratio of 10:1-2 by weight to obtain a quaternary silver-cerium-doped titanium dioxide intermediate, and then the quaternary silver-cerium-doped titanium dioxide intermediate is reacted with the coupling agent at an addition ratio of 50:1-2 by weight to obtain the fabric.
[0005] By adopting the above technical scheme, cotton fiber plays a role of absorbing water in highly absorbent antibacterial fabrics and can quickly absorb water. Bamboo charcoal fiber has a super strong adsorption and decomposition ability due to the honeycomb microporous structure running through the inside and outside of bamboo charcoal fiber and a surface area several times larger than that of charcoal. It can effectively remove human sweat odor and has the functions of antibacterial, regulating humidity and eliminating odor; it also has an adsorption effect on harmful chemicals such as sulfides and nitrides; bamboo charcoal can also produce infrared rays suitable for human absorption, increase blood circulation, and increase the negative ions in the air that are beneficial to health. Polyester has water-washing resistance and can improve the durability of fabrics. Hydrophilic finishing agents can make fabrics have better hydrophilicity, absorb moisture and dry quickly. Quaternary ammonium modified composite antibacterial agents with active functional groups are the antibacterial components of fabrics, which can effectively kill bacteria and fungi, keep fabrics clean, and also have the function of repelling mites. The synergistic effect between the components is that cotton fiber, bamboo charcoal fiber and polyester together constitute the basic structure of the fabric, and can achieve the comprehensive properties of water absorption, antibacterial and durability. The hydrophilic finishing agent makes the fabric hydrophilic and can increase the water absorption speed. The quaternary ammonium modified composite antibacterial agent with active functional groups forms an antibacterial layer on the surface of the fabric, which effectively interacts with bacteria and keeps the fabric hygienic. Overall, the various components cooperate with each other to form a highly water-absorbent and antibacterial functional fabric.
[0006] Preferably, the hydrophilic finishing agent is prepared from p-dimethylaminobenzaldehyde, methoxyphenylmethanol and propylene oxide ethyl ether.
[0007] Preferably, the preparation method of the hydrophilic finishing agent comprises the following steps: S31, adding p-dimethylaminobenzaldehyde, tetrabutylammonium bromide and chloroform into the reactor in a mass ratio of 1:0.082:9.12, stirring and dissolving, heating to 43°C, adding 650% sodium hydroxide with a mass concentration of 1.75 times the mass of p-dimethylaminobenzaldehyde at a rate of 8 drops / min, maintaining the temperature at 50°C, stirring at 300rpm for 5.5-6h, cooling to room temperature, filtering, washing with chloroform 3 times, adding 10% hydrochloric acid with a mass concentration until the solution pH is 4-5, extracting, adding anhydrous sodium sulfate with a mass concentration of 9.3 times the mass of p-dimethylaminobenzaldehyde, drying for 10-12h, 300rpm, 52°C rotary evaporation for 4-6h, to obtain oxidized p-dimethylaminobenzaldehyde; S32, adding oxidized p-dimethylaminobenzaldehyde, methoxyphenylmethanol and boron trifluoride etherate in a mass ratio of 1:0.56:4.65 to a reactor, stirring to dissolve, stirring at 32°C and 300rpm for 10 hours, cooling to room temperature, adding 0°C ice water with a mass of 20.51 times that of oxidized p-dimethylaminobenzaldehyde, stirring until no solid appears, filtering, washing with saturated sodium bicarbonate 6 times, washing with distilled water until the pH of the solution is 6.5-7, and drying at room temperature for 11-12 hours to obtain a furanone compound; S33. Add furanone compound and propylene oxide ethyl ether into the reactor in a mass ratio of 1:1.7, heat it to 173°C, add isopropyl titanate in an amount of 0.023 times the mass of furanone compound, heat it to 215°C at a rate of 1.2°C / min, react for 6-7h, heat it to 298°C, evacuate to 100Pa, react for 16-18h, and obtain a hydrophilic finishing agent.
[0008] By adopting the above technical scheme, the hydrophilic finishing agent is firstly oxidized to carboxyl and hydroxyl groups of p-dimethylaminobenzaldehyde, and then reacted with the hydroxyl group of methoxyphenylmethanol to form furanone groups; in the hydrophilic finishing agent, the epoxy group and the furanone group are ring-opening polymerized to form an ester ether structure, which is similar to the chain segment of cotton fiber, and can be eutectic and co-crystallized with the cotton fiber during the finishing process, generating a strong force, forming a film on the surface of the cotton fiber fabric, covering the cotton fiber, so that the hydrophilic moisture absorption finishing has good durability; the polyester-polyether copolymer chain segment of the hydrophilic finishing agent is hydrophilic, so that the bath towel has water absorption, and at the same time, the para-position and meta-position molecular structures of p-dimethylaminobenzaldehyde and methoxyphenylmethanol destroy the regularity of the molecular structure of the copolymer chain segment of the self-made hydrophilic finishing agent, reduce the degree of crystallization, and are conducive to the adsorption of water molecules, thereby improving the water absorption of the bath towel, and introducing multiple hydrophilic groups to enhance the water absorption of the bath towel.
[0009] Preferably, the method for preparing silver-cerium doped titanium dioxide comprises the following steps: S41. At room temperature, add 100 mL of tetra-n-butyl titanate to 180 mL of ethanol and stir for 20 min to form solution A. S42, adding 2.0 g of silver nitrate and 3.5 g of cerium nitrate to a solution consisting of 100 mL of ethanol, 30 mL of acetic acid and 100 mL of water to form solution B; S43. Add solution B dropwise into solution A, stir for 20-30 min, heat to 45°C, let stand for 12 h, then centrifuge, wash, dry at 85°C for 8 h, and finally calcine at 500°C for 3.5 h, cool, grind, and sieve to obtain silver-cerium-doped titanium dioxide, the particle size of which is 0.12-0.3 μm.
[0010] By adopting the above technical solution, in this application, the role of silver-cerium doped titanium dioxide is to enhance the antibacterial performance, and it has the functions of antibacterial, deodorizing and repelling mites. The silver-cerium doped titanium dioxide obtained by the above preparation method has a nanometer-scale particle size, which increases its surface area, is conducive to contact with bacteria and other microorganisms and exerts an antibacterial effect, and also enhances its dispersibility and stability in the fabric. On the whole, in the highly water-absorbent antibacterial bath towel fabric, the silver-cerium doped titanium dioxide, as part of the quaternary ammonium modified composite antibacterial agent with active functional groups, synergizes with raw materials such as cotton fiber, bamboo charcoal fiber, polyester and hydrophilic finishing agent, and jointly achieves excellent water absorption performance, antibacterial, long-lasting deodorization and water washability, providing a comprehensive care function for the bath towel fabric.
[0011] Preferably, the preparation method of the quaternary ammonium modified composite antibacterial agent with active functional groups comprises the following steps: S51, ultrasonically dispersing silver cerium doped titanium dioxide in an ethanol solution, then adding a quaternary ammonium salt, reacting at 72° C. for 18-22 hours, centrifuging to remove the supernatant after the reaction is completed, and ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted quaternary ammonium salt, to obtain a quaternary ammonium modified composite antibacterial agent intermediate; S52. Ultrasonic dispersion of the obtained quaternary ammonium modified composite antibacterial agent intermediate in an ethanol solution, adding a coupling agent, reacting at 40°C for 30-36 hours, centrifuging to remove the supernatant after the reaction is completed, ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted coupling agent, and freeze-drying to obtain a quaternary ammonium modified composite antibacterial agent with active functional groups.
[0012] By adopting the above technical scheme, in the present application, the role of the quaternary ammonium modified composite antibacterial agent with active functional groups is multifaceted, and it works in synergy with other raw materials to achieve efficient antibacterial effects and other functions: by allowing the hydrophobic molecular chain of the quaternary ammonium salt to pierce the phospholipid bilayer of the bacterial capsule, the dissolution of the bacterial capsule and the leakage of the cytosol are caused, which eventually leads to the death of the bacteria. The added silver cerium doped titanium dioxide enhances the antibacterial performance, and through the modified composite antibacterial agent, new active sites are given, so that a chemical reaction occurs with the substrate, thereby improving the antibacterial effect. Together with materials such as bamboo charcoal fiber and polyester, excellent antibacterial, deodorizing and mite-repelling functions are achieved. It reacts with the oxygen-containing functional groups produced on the polyester surface to form covalent bond binding force, van der Waals force, electrostatic binding force, etc., making the antibacterial property more resistant to washing and not easy to fall off. In general, quaternary ammonium modified composite antibacterial agents with active functional groups play an important role in highly absorbent and antibacterial bath towel fabrics. By synergizing with other raw materials, they provide multiple care functions for bath towel fabrics, keep the fabrics clean and hygienic, and enhance the user experience.
[0013] Preferably, in step S51, the mass ratio of the quaternary ammonium salt to silver-cerium-doped titanium dioxide is 10:1-2.
[0014] Preferably, in step S52, the mass ratio of the quaternary ammonium silver cerium doped titanium dioxide intermediate to the coupling agent is 50:1-2.
[0015] Preferably, the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1-2.
[0016] Preferably, the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 1:2:4-5.
[0017] By adopting the above technical scheme, the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and its main function is to help the quaternary ammonium silver cerium doped titanium dioxide intermediate form a strong chemical bond with the polyester substrate. This can increase the adhesion of the antibacterial agent on the fabric, improve its washability and durability. In addition, the synergistic effect between the coupling agent and the quaternary ammonium silver cerium doped titanium dioxide intermediate is as follows: in the process of preparing the quaternary ammonium silver cerium doped titanium dioxide intermediate, the addition of the coupling agent can promote the reaction, facilitate the formation of the intermediate, and increase the antibacterial performance. The coupling agent contains different functional groups, which can provide more chemical reaction sites for the quaternary ammonium silver cerium doped titanium dioxide intermediate, which is conducive to the combination with the substrate and the linking of the active functional groups, and enhances the overall performance of the material. The active functional groups such as hydroxyl and epoxy in the coupling agent react chemically with the oxygen-containing functional groups on the surface of the substrate to form a stable covalent bond, which improves the bonding strength between the antibacterial agent and the substrate, thereby enhancing the washability and durability of the antibacterial bath towel fabric. Due to the synergistic effect between quaternized silver cerium doped titanium dioxide and the coupling agent, the bath towel fabric has better antibacterial properties, washability and durability, further improving the quality and performance of the product, meeting the needs of modern consumers for functional bath towels.
[0018] In the second aspect, the present application provides a method for preparing a highly absorbent antibacterial bath towel fabric, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned highly absorbent antibacterial bath towel fabric, comprising the following steps: S101, modifying the polyester by oxygen plasma treatment according to the mass fraction to obtain surface-modified polyester; S102, dispersing the quaternary ammonium modified composite antibacterial agent with active functional groups in 100 parts of deionized water according to the mass fraction, hydrolyzing for 30 hours to form a hydrolyzate, and then immersing and rolling the surface-modified polyester in the hydrolyzate to obtain a modified polyester; S103. Immerse the cotton fiber in a solution consisting of a hydrophilic finishing agent and deionized water 3 times the mass of the hydrophilic finishing agent according to the mass fraction, heat it to 35°C, immerse it for 30 minutes, centrifuge it at 2000rpm for 10 minutes, and then dry it at 105 for 20 minutes to obtain hydrophilic finished cotton fiber; send the hydrophilic finished cotton fiber to a sizing machine, sizing it for 2-3 minutes, and then add bamboo charcoal fiber and modified polyester blend at the same time to weave a fabric precursor; immerse the fabric precursor in deionized water 10 times the mass of the cotton fiber, control the temperature at 112°C, boil it for 8-10 minutes, send it to a dryer, and dry it at 102°C for 8-12 minutes to obtain a highly absorbent antibacterial bath towel fabric.
[0019] By adopting the above technical scheme, the surface of the polyester pretreated with oxygen plasma will produce oxygen-containing functional groups such as hydroxyl, ether and carbonyl groups, and the quaternary ammonium modified composite antibacterial agent with active functional groups will react with it, and there will be covalent bond binding force, van der Waals force, electrostatic binding force, etc. between them, making its antibacterial property more resistant to washing and not easy to fall off. The preparation method provided by this application is simple in process, green and environmentally friendly, with high production efficiency, and is conducive to large-scale manufacturing and production.
[0020] In summary, the beneficial technical effects of this application are: 1. Excellent water absorption performance: The active functional groups such as hydroxyl and ether groups in the hydrophilic finishing agent form a strong force with the surface of cotton fibers, which improves the water absorption performance of the bath towel. At the same time, the addition of appropriate polyester content and bamboo charcoal fiber is also conducive to improving the water absorption effect, making the bath towel have better water absorption and quick drying characteristics.
[0021] 2. Antibacterial and long-lasting deodorization performance: The quaternary ammonium modified composite antibacterial agent with active functional groups has excellent antibacterial effect, which can effectively prevent the reproduction of bacteria and fungi, thereby keeping the bath towel clean and hygienic. At the same time, this antibacterial agent can also deodorize for a long time and effectively remove odors such as sweat.
[0022] 3. Washing resistance: The copolymer segments in the hydrophilic finishing agent have good durability and can form a stable film on the surface of the bath towel, improving the wash resistance of the fabric. In addition, the content and treatment of polyester can also make the bath towel more durable.
[0023] 4. Anti-mite effect: The ingredients of the quaternary ammonium modified composite antibacterial agent can effectively kill fungi, block the food source of mites, achieve the effect of anti-mite, and increase the hygiene of the bath towel. DETAILED DESCRIPTION
[0024] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0025] Preparation Example 1: Preparation of a hydrophilic finishing agent The preparation method of a hydrophilic finishing agent comprises the following steps: S31, adding p-dimethylaminobenzaldehyde, tetrabutylammonium bromide and chloroform into the reactor in a mass ratio of 1:0.082:9.12, stirring and dissolving, heating to 43°C, adding 650% sodium hydroxide with a mass concentration of 1.75 times the mass of p-dimethylaminobenzaldehyde at a rate of 8 drops / min, maintaining the temperature at 50°C, stirring at 300rpm for 6h, cooling to room temperature, filtering, washing with chloroform 3 times, adding 10% hydrochloric acid with a mass concentration until the solution pH is 4.5, extracting, adding anhydrous sodium sulfate with a mass concentration of 9.3 times the mass of p-dimethylaminobenzaldehyde, drying for 12h, 300rpm, 52°C rotary evaporation for 6h, to obtain oxidized p-dimethylaminobenzaldehyde; S32, adding oxidized p-dimethylaminobenzaldehyde, methoxyphenylmethanol and boron trifluoride etherate in a mass ratio of 1:0.56:4.65 to a reactor, stirring to dissolve, stirring at 32°C and 300rpm for 10 hours, cooling to room temperature, adding 0°C ice water with a mass of 20.51 times that of oxidized p-dimethylaminobenzaldehyde, stirring until no solid appears, filtering, washing with saturated sodium bicarbonate 6 times, washing with distilled water until the solution pH is 7, and drying at room temperature for 12 hours to obtain a furanone compound; S33. Add furanone compound and propylene oxide ethyl ether into the reactor in a mass ratio of 1:1.7, heat to 173°C, add isopropyl titanate in an amount of 0.023 times the mass of furanone compound, heat to 215°C at a rate of 1.2°C / min, react for 7h, heat to 298°C, evacuate to 100Pa, react for 17h, and obtain a hydrophilic finishing agent.
[0026] The hydrophilic finishing agent prepared above was used in various examples and comparative examples.
[0027] Preparation Example 2: Preparation of Silver-Cerium-Doped Titanium Dioxide The preparation method of silver-cerium doped titanium dioxide comprises the following steps: S41. At room temperature, add 100 mL of tetra-n-butyl titanate to 180 mL of ethanol and stir for 20 min to form solution A. S42, adding 2.0 g of silver nitrate and 3.5 g of cerium nitrate to a solution consisting of 100 mL of ethanol, 30 mL of acetic acid and 100 mL of water to form solution B; S43. Add solution B dropwise into solution A, stir for 20-30 min, heat to 45°C, let stand for 12 h, then centrifuge, wash, dry at 85°C for 8 h, and finally calcine at 500°C for 3.5 h, cool, grind, and sieve to obtain silver-cerium-doped titanium dioxide, the particle size of which is 0.12-0.3 μm.
[0028] The silver-cerium-doped titanium dioxide prepared above was used in Preparation Examples 3 to 5 and various comparative preparation examples.
[0029] Preparation Example 3: Preparation of quaternary ammonium modified composite antibacterial agent with active functional groups The preparation method of the quaternary ammonium modified composite antibacterial agent with active functional groups comprises the following steps: S51, ultrasonically dispersing silver cerium doped titanium dioxide in an ethanol solution, then adding a quaternary ammonium salt, reacting at 72°C for 18 hours, centrifuging to remove the supernatant after the reaction is completed, using a 75% ethanol solution and pure water for ultrasonic washing three times respectively to fully remove the unreacted quaternary ammonium salt, and obtaining a quaternary ammonium modified composite antibacterial agent intermediate; the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1; the mass ratio of the quaternary ammonium salt to the silver cerium doped titanium dioxide is 10:1; S52. Ultrasonic dispersion of the obtained quaternary ammonium modified composite antibacterial agent intermediate in an ethanol solution, adding a coupling agent, reacting at 40°C for 30 hours, centrifuging to remove the supernatant after the reaction is completed, ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted coupling agent, and freeze-drying to obtain a quaternary ammonium modified composite antibacterial agent with active functional groups; the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:2:4; the mass ratio of the quaternary ammonium silver cerium doped titanium dioxide intermediate to the coupling agent is 50:1.
[0030] Preparation Example 4: Preparation of quaternary ammonium modified composite antibacterial agent with active functional groups The preparation method of the quaternary ammonium modified composite antibacterial agent with active functional groups comprises the following steps: S51, ultrasonically dispersing silver cerium doped titanium dioxide in an ethanol solution, then adding a quaternary ammonium salt, reacting at 72°C for 22 hours, centrifuging to remove the supernatant after the reaction is completed, using a 75% ethanol solution and pure water for ultrasonic washing three times respectively to fully remove the unreacted quaternary ammonium salt, and obtaining a quaternary ammonium modified composite antibacterial agent intermediate; the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:2; the mass ratio of the quaternary ammonium salt to silver cerium doped titanium dioxide is 10:2; S52. Ultrasonic dispersion of the obtained quaternary ammonium modified composite antibacterial agent intermediate in an ethanol solution, adding a coupling agent, reacting at 40°C for 36 hours, centrifuging to remove the supernatant after the reaction is completed, ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted coupling agent, and freeze-drying to obtain a quaternary ammonium modified composite antibacterial agent with active functional groups; the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:2:5; the mass ratio of the quaternary ammonium silver cerium doped titanium dioxide intermediate to the coupling agent is 50:2.
[0031] Preparation Example 5: Preparation of quaternary ammonium modified composite antibacterial agent with active functional groups The preparation method of the quaternary ammonium modified composite antibacterial agent with active functional groups comprises the following steps: S51, ultrasonically dispersing silver cerium doped titanium dioxide in an ethanol solution, then adding a quaternary ammonium salt, reacting at 72°C for 20 hours, centrifuging to remove the supernatant after the reaction is completed, using a 75% ethanol solution and pure water for ultrasonic washing three times respectively to fully remove the unreacted quaternary ammonium salt, and obtaining a quaternary ammonium modified composite antibacterial agent intermediate; the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1.5; the mass ratio of the quaternary ammonium salt to silver cerium doped titanium dioxide is 10:1.5; S52. Ultrasonic dispersion of the obtained quaternary ammonium modified composite antibacterial agent intermediate in an ethanol solution, adding a coupling agent, reacting at 40°C for 33 hours, centrifuging to remove the supernatant after the reaction is completed, ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted coupling agent, and freeze-drying to obtain a quaternary ammonium modified composite antibacterial agent with active functional groups; the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:2:4.5; the mass ratio of the quaternary ammonium silver cerium doped titanium dioxide intermediate to the coupling agent is 50:1.5.
[0032] Preparation Comparative Example 1: The preparation of a quaternary ammonium modified composite antibacterial agent with an active functional group is the same as that of Preparation Example 5, except that an equal amount of γ-glycidyloxypropyltrimethoxysilane is used instead of a coupling agent, and the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 1:2:4.5.
[0033] Preparation Comparative Example 2: The preparation of a quaternary ammonium modified composite antibacterial agent with an active functional group is the same as that of Preparation Example 5, except that an equal amount of vinyl triethoxy silane is used instead of a coupling agent, and the coupling agent is composed of γ-glycidyloxypropyl trimethoxy silane, vinyl triethoxy silane and γ-(2,3-epoxypropyloxy)propyl trimethoxy silane in a mass ratio of 1:2:4.5.
[0034] Preparation Comparative Example 3: The preparation of a quaternary ammonium modified composite antibacterial agent with an active functional group is the same as that of Preparation Example 5, except that an equal amount of γ-(2,3-epoxypropoxy)propyltrimethoxysilane is used instead of a coupling agent, and the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:2:4.5.
[0035] Preparation Comparative Example 4: Preparation of quaternary ammonium modified composite antibacterial agent with active functional groups The same as Preparation Example 5, except that an equal amount of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride is used instead of a quaternary ammonium salt, and the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1.5.
[0036] Preparation Comparative Example 5: Preparation of quaternary ammonium modified composite antibacterial agent with active functional groups The same as Preparation Example 5, except that an equal amount of 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride is used instead of a quaternary ammonium salt, and the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1.5.
[0037] Example 1 A highly absorbent antibacterial bath towel fabric, comprising the following raw materials by weight: 4.5 kg of cotton fiber, 3.6 kg of bamboo charcoal fiber, 5.6 kg of polyester, 2.5 kg of hydrophilic finishing agent, and 0.6 kg of quaternary ammonium modified composite antibacterial agent with active functional groups; the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example 3; The above-mentioned method for preparing a highly water-absorbent antibacterial bath towel fabric comprises the following steps: S101, modifying the polyester by oxygen plasma treatment according to the mass fraction to obtain surface-modified polyester; S102, dispersing the quaternary ammonium modified composite antibacterial agent with active functional groups in 10 kg of deionized water according to the mass fraction, hydrolyzing for 30 hours to form a hydrolyzate, and then immersing and rolling the surface-modified polyester in the hydrolyzate to obtain a modified polyester; S103. Immerse the cotton fiber in a solution consisting of a hydrophilic finishing agent and deionized water 3 times the mass of the hydrophilic finishing agent according to the mass fraction, heat it to 35°C, immerse it for 30 minutes, centrifuge it at 2000rpm for 10 minutes, and then dry it at 105 for 20 minutes to obtain hydrophilic finished cotton fiber; send the hydrophilic finished cotton fiber to a sizing machine, sizing it for 2 minutes, and then add bamboo charcoal fiber and modified polyester blend at the same time to weave a fabric precursor; immerse the fabric precursor in deionized water 10 times the mass of the cotton fiber, control the temperature at 112°C, boil it for 8 minutes, send it to a dryer, and dry it at 102°C for 8 minutes to obtain a highly absorbent antibacterial bath towel fabric.
[0038] Example 2 A highly absorbent antibacterial bath towel fabric, comprising the following raw materials by weight: 4.5 kg of cotton fiber, 3.6 kg of bamboo charcoal fiber, 5.6 kg of polyester, 2.5 kg of hydrophilic finishing agent, and 0.6 kg of quaternary ammonium modified composite antibacterial agent with active functional groups; the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example 4; The above-mentioned method for preparing a highly water-absorbent antibacterial bath towel fabric comprises the following steps: S101, modifying the polyester by oxygen plasma treatment according to the mass fraction to obtain surface-modified polyester; S102, dispersing the quaternary ammonium modified composite antibacterial agent with active functional groups in 10 kg of deionized water according to the mass fraction, hydrolyzing for 30 hours to form a hydrolyzate, and then immersing and rolling the surface-modified polyester in the hydrolyzate to obtain a modified polyester; S103. Immerse the cotton fiber in a solution consisting of a hydrophilic finishing agent and deionized water 3 times the mass of the hydrophilic finishing agent according to the mass fraction, heat it to 35°C, immerse it for 30 minutes, centrifuge it at 2000rpm for 10 minutes, and then dry it at 105 for 20 minutes to obtain hydrophilic finished cotton fiber; send the hydrophilic finished cotton fiber to a sizing machine, sizing it for 3 minutes, and then add bamboo charcoal fiber and modified polyester blend at the same time to weave a fabric precursor; immerse the fabric precursor in deionized water 10 times the mass of the cotton fiber, control the temperature at 112°C, boil it for 10 minutes, send it to a dryer, and dry it at 102°C for 12 minutes to obtain a highly absorbent antibacterial bath towel fabric.
[0039] Example 3 A highly absorbent antibacterial bath towel fabric, comprising the following raw materials by weight: 4.3 kg of cotton fiber, 3.3 kg of bamboo charcoal fiber, 5.3 kg of polyester, 2.2 kg of a hydrophilic finishing agent, and 0.55 kg of a quaternary ammonium modified composite antibacterial agent with an active functional group; the quaternary ammonium modified composite antibacterial agent with an active functional group is prepared by Preparation Example 5; The above-mentioned method for preparing a highly water-absorbent antibacterial bath towel fabric comprises the following steps: S101, modifying the polyester by oxygen plasma treatment according to the mass fraction to obtain surface-modified polyester; S102, dispersing the quaternary ammonium modified composite antibacterial agent with active functional groups in 10 kg of deionized water according to the mass fraction, hydrolyzing for 30 hours to form a hydrolyzate, and then immersing and rolling the surface-modified polyester in the hydrolyzate to obtain a modified polyester; S103. Immerse the cotton fiber in a solution consisting of a hydrophilic finishing agent and deionized water 3 times the mass of the hydrophilic finishing agent according to the mass fraction, heat it to 35°C, immerse it for 30 minutes, centrifuge it at 2000rpm for 10 minutes, and then dry it at 105 for 20 minutes to obtain hydrophilic finished cotton fiber; send the hydrophilic finished cotton fiber to a sizing machine, sizing it for 3 minutes, and then add bamboo charcoal fiber and modified polyester blend at the same time to weave a fabric precursor; immerse the fabric precursor in deionized water 10 times the mass of the cotton fiber, control the temperature at 112°C, boil it for 9 minutes, send it to a dryer, and dry it at 102°C for 10 minutes to obtain a highly absorbent antibacterial bath towel fabric.
[0040] Example 4 The same as Example 3, except that: the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example Comparative Example 1.
[0041] Example 5 The same as Example 3, except that: the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example Comparative Example 2.
[0042] Example 6 The same as Example 3, except that: the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example Comparative Example 3.
[0043] Example 7 The same as Example 3, except that: the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example Comparative Example 4.
[0044] Example 8 The same as Example 3, except that: the quaternary ammonium modified composite antibacterial agent with active functional groups is prepared by Preparation Example Comparative Example 5.
[0045] Comparative Example 1 The same as Example 3, except that an equal amount of deionized water is used instead of the quaternary ammonium modified composite antibacterial agent with active functional groups.
[0046] Comparative Example 2 The same as Example 3, except that an equal amount of deionized water is used instead of the hydrophilic finishing agent.
[0047] Performance Testing The following performance tests were performed on the highly water-absorbent antibacterial bath towel fabrics prepared in Examples 1 to 8 and Comparative Examples 1 to 2 of the present application; Antibacterial performance test: According to GB / T 20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method, the test bacteria are Escherichia coli 8099 and Staphylococcus aureus ATCC 6538, and the results are shown in Table 1; Washing resistance test: AATCC 1993WOB detergent was used to wash 50 times according to the method in Appendix C of the standard "FZ / T 73023-2006 Antibacterial knitwear", and then dried. The experiment was carried out according to "GB / T 20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", and the test bacteria were Escherichia coli 8099 and Staphylococcus aureus ATCC 6538. The results are shown in Table 1; Water absorption test: refer to the method 8.1 in GB / T21655.1 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Unidirectional combined test method" for measurement. The results are shown in Table 2. Deodorization performance test: According to GB / T 33610.2-2017 Determination of deodorization performance of textiles Part 2: Detection tube method, the samples were tested for deodorization performance of ammonia and acetic acid. The results are shown in Table 2. Anti-mite performance test: The anti-mite performance of the samples was tested according to the avoidance method in "GB / T 24253-2009 Evaluation of Anti-mite Performance of Textiles". The results are shown in Table 2.
[0048] Table 1 Antibacterial and water-resistant performance test table Table 2 Water absorption, deodorization and anti-mite performance test table Analyzing the data in Table 1 and Table 2, we can see that: 1) In combination with Examples 1 to 3, it can be seen that the careful proportioning and interaction of various raw materials in the present application make the bath towel fabric have multiple functions. It not only has excellent water absorption and antibacterial properties, but also has the characteristics of water resistance, long-lasting deodorization and anti-mite, providing consumers with a healthier, more hygienic and comfortable use experience.
[0049] 2) The performance comparison analysis of Example 3 and Example 4-Example 6 shows that the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane. By utilizing the synergistic effect between them, the active functional groups such as hydroxyl and epoxy groups in the coupling agent react chemically with the oxygen-containing functional groups on the surface of the substrate to form a stable covalent bond, thereby improving the bonding strength between the antibacterial agent and the substrate, thereby enhancing the washability and durability of the antibacterial bath towel fabric. Due to the synergistic effect between quaternized silver cerium doped titanium dioxide and the coupling agent, the bath towel fabric has better antibacterial performance, washability and durability, further improving the quality and performance of the product, and meeting the needs of modern consumers for functional bath towels.
[0050] 3) From the comparative analysis of the performance of Example 3 and Example 7-Example 8, it can be seen that the quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1.5, and the synergistic effect between them can improve the comprehensive performance of the highly absorbent antibacterial bath towel fabric.
[0051] 4) The performance comparison analysis of Example 3 and Comparative Example 1 shows that the quaternary ammonium modified composite antibacterial agent with active functional groups prepared by the present application has many aspects, and works in synergy with other raw materials to achieve efficient antibacterial effect and other functions: by allowing the hydrophobic molecular chain of the quaternary ammonium salt to pierce the phospholipid bilayer of the bacterial capsule, causing the dissolution of the bacterial capsule and the leakage of the cytosol, ultimately leading to bacterial death. The added silver cerium doped titanium dioxide enhances the antibacterial performance, and through the modified composite antibacterial agent, a new active site is given, so that a chemical reaction occurs with the substrate, thereby improving the antibacterial effect. Together with materials such as bamboo charcoal fiber and polyester, excellent antibacterial, deodorizing and mite-repelling functions are achieved. Reacting with the oxygen-containing functional groups produced on the polyester surface, covalent bond binding force, van der Waals force, electrostatic binding force, etc. are formed, making the antibacterial property more resistant to washing and not easy to fall off.
[0052] 5) It can be seen from the performance comparison analysis of Example 3 and Comparative Example 2 that the hydrophilic finishing agent prepared in the present application is first oxidized to carboxyl and hydroxyl groups of the aldehyde group of p-dimethylaminobenzaldehyde, and then reacted with the hydroxyl group of methoxyphenylmethanol to form a furanone group; in the hydrophilic finishing agent, the epoxy group and the furanone group are ring-opening polymerized to form an ester ether structure, which is similar to the chain segment of cotton fiber. During the finishing process, it can co-melt and co-crystallize with the cotton fiber, generate a strong force, form a film on the surface of the cotton fiber fabric, and cover the cotton fiber, so that the hydrophilic moisture absorption finishing has good durability; the polyester-polyether copolymer chain segment of the hydrophilic finishing agent is hydrophilic, which makes the bath towel absorbent. At the same time, the para- and meta-molecular structures of p-dimethylaminobenzaldehyde and methoxyphenylmethanol destroy the regularity of the molecular structure of the copolymer chain segment of the homemade hydrophilic finishing agent, reduce the degree of crystallization, and are conducive to the adsorption of water molecules, improve the water absorption of the bath towel, and introduce multiple hydrophilic groups to increase the water absorption of the bath towel.
[0053] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A highly water-absorbent antibacterial bath towel fabric, characterized in that: The invention comprises the following raw materials by weight: 40-45 parts of cotton fiber, 30-36 parts of bamboo charcoal fiber, 50-56 parts of polyester, 20-25 parts of hydrophilic finishing agent and 5-6 parts of quaternary ammonium modified composite antibacterial agent with active functional groups, wherein the quaternary ammonium modified composite antibacterial agent with active functional groups uses silver cerium doped titanium dioxide, quaternary ammonium salt and coupling agent as main raw materials, firstly, the quaternary ammonium salt and silver cerium doped titanium dioxide are reacted at a mass ratio of 10:1-2 to prepare a quaternary silver cerium doped titanium dioxide intermediate, and then the quaternary silver cerium doped titanium dioxide intermediate is reacted with the coupling agent at a mass ratio of 50:1-2 to prepare the quaternary silver cerium doped titanium dioxide intermediate.
2. The highly water-absorbent antibacterial bath towel fabric according to claim 1, characterized in that: The hydrophilic finishing agent is prepared from p-dimethylaminobenzaldehyde, methoxyphenylmethanol and propylene oxide ethyl ether.
3. The highly water-absorbent antibacterial bath towel fabric according to claim 1, characterized in that: The preparation method of silver-cerium doped titanium dioxide comprises the following steps: S31. At room temperature, add 100 mL of tetra-n-butyl titanate to 180 mL of ethanol and stir for 20 min to form solution A. S32, adding 2.0 g of silver nitrate and 3.5 g of cerium nitrate to a solution consisting of 100 mL of ethanol, 30 mL of acetic acid and 100 mL of water to form solution B; S33. Add solution B dropwise into solution A, stir for 20-30 min, heat to 45°C, let stand for 12 h, then centrifuge, wash, dry at 85°C for 8 h, and finally calcine at 500°C for 3.5 h, cool, grind, and sieve to obtain silver-cerium-doped titanium dioxide, the particle size of which is 0.12-0.3 microns.
4. The highly water-absorbent antibacterial bath towel fabric according to claim 1, characterized in that: The preparation method of the quaternary ammonium modified composite antibacterial agent with active functional groups comprises the following steps: S41, ultrasonically dispersing silver cerium doped titanium dioxide in an ethanol solution, then adding a quaternary ammonium salt, reacting at 72° C. for 18-22 hours, centrifuging to remove the supernatant after the reaction is completed, and ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted quaternary ammonium salt, to obtain a quaternary ammonium modified composite antibacterial agent intermediate; S42. Ultrasonic dispersion of the obtained quaternary ammonium modified composite antibacterial agent intermediate in an ethanol solution, adding a coupling agent, reacting at 40°C for 30-36 h, centrifuging to remove the supernatant after the reaction is completed, ultrasonically washing three times with a 75% ethanol solution and pure water respectively to fully remove the unreacted coupling agent, and freeze-drying to obtain a quaternary ammonium modified composite antibacterial agent with active functional groups.
5. The highly water-absorbent antibacterial bath towel fabric according to claim 4, characterized in that: In step S41, the mass ratio of the quaternary ammonium salt to silver-cerium-doped titanium dioxide is 10:1-2.
6. The highly water-absorbent antibacterial bath towel fabric according to claim 4, characterized in that: In step S42, the mass ratio of the quaternary ammonium silver cerium doped titanium dioxide intermediate to the coupling agent is 50:1-2.
7. The highly water-absorbent antibacterial bath towel fabric according to claim 4, characterized in that: The quaternary ammonium salt is composed of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride in a mass ratio of 3:1-2.
8. The highly water-absorbent antibacterial bath towel fabric according to claim 4, characterized in that: The coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane in a mass ratio of 1:2:4-5.
9. A method for preparing a highly water-absorbent antibacterial bath towel fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: S91, modifying the polyester by oxygen plasma treatment according to the mass fraction to obtain surface-modified polyester; S92, dispersing the quaternary ammonium modified composite antibacterial agent with active functional groups in 100 parts of deionized water according to the mass fraction, hydrolyzing for 30 hours to form a hydrolyzate, and then immersing and rolling the surface-modified polyester in the hydrolyzate to obtain a modified polyester; S93. According to the mass fraction, the cotton fiber is immersed in a solution consisting of a hydrophilic finishing agent and deionized water 3 times the mass of the hydrophilic finishing agent, the temperature is raised to 35°C, and after immersion for 30 minutes, the solution is centrifuged and dehydrated at 2000 rpm for 10 minutes, and then dried at 105 for 20 minutes to obtain hydrophilic finished cotton fiber; the hydrophilic finished cotton fiber is sent to a sizing machine, sizing for 2-3 minutes, and then bamboo charcoal fiber and modified polyester are added at the same time to weave a fabric precursor; the fabric precursor is immersed in deionized water 10 times the mass of the cotton fiber, the temperature is controlled at 112°C, boiled for 8-10 minutes, sent to a dryer, and dried at 102°C for 8-12 minutes to obtain a highly absorbent antibacterial bath towel fabric.
Citation Information
Cited By
Moisture-absorbing antibacterial fabric and preparation method thereof
CN119711027A
A kind of moisture-absorbing antibacterial fabric and preparation method thereof
CN119711027B
